2022
DOI: 10.3390/ijerph192114444
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Changes in Physical and Motor Development Observed among Physiotherapy Students from Bydgoszcz in 2011–2020

Abstract: Introduction: The aim of the study is to assess the changes in somatic and motor characteristics in adolescents studying physiotherapy from 2011–2020. It was hypothesized that there was no secular trend of morphological features, its maintenance in endurance, increased sexual dimorphism and the influence of the COVID-19 pandemic on the observed characteristics. Materials and methods: Young people studying at the Collegium Medicum in Bydgoszcz were examined. Basic somatic features, endurance and coordination we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Previously, secular trends of increasing body height and mass, accompanied by a weaker body structure, were found 15 , 31 , 32 . Some of the studies showed a secular trend of an increasing BMI among Polish students, which contradicts the trends for this indicator in the currently analysed groups of female students in the 2011–2020 decade 18 , 32 . Among the currently examined characteristics, there were also trends towards a decrease in the thickness of the skinfold over the biceps and of that measured over the calf among men, which may indicate a greater activity involving the limbs, especially the upper limbs, than that involving the other parts of the body.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previously, secular trends of increasing body height and mass, accompanied by a weaker body structure, were found 15 , 31 , 32 . Some of the studies showed a secular trend of an increasing BMI among Polish students, which contradicts the trends for this indicator in the currently analysed groups of female students in the 2011–2020 decade 18 , 32 . Among the currently examined characteristics, there were also trends towards a decrease in the thickness of the skinfold over the biceps and of that measured over the calf among men, which may indicate a greater activity involving the limbs, especially the upper limbs, than that involving the other parts of the body.…”
Section: Discussionmentioning
confidence: 74%
“…However, the main aim of this study was to determine the magnitude of changes in the examined somatic features and indicators of motor skills conducive to health over a period of two decades of observation. For the observed somatic features, secular trends of the decreased age in men and increased body mass in women, as well as the stability of the body height in both sexes, were found in the student groups 18 . In terms of the body height and mass of female students, the results obtained do not clearly correspond to those of secular trends in other student groups, especially those studied in earlier decades.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…From the research on the physical tness of physiotherapy students, it is known that it differs from that of students at physical education universities and other universities undertaking education in this eld. Some of its components deteriorate [12][13][14][15][16]. However, most of the scienti c reports on changes in physical tness come from cross-sectional and comparative studies and less often from long-term studies of secular trends.…”
Section: Introductionmentioning
confidence: 99%